2016
DOI: 10.1007/s00394-016-1187-z
|View full text |Cite
|
Sign up to set email alerts
|

Dietary polyphenols are inversely associated with metabolic syndrome in Polish adults of the HAPIEE study

Abstract: PurposeThe aim of this study was to evaluate the association between total and individual classes and subclasses of dietary polyphenol intake and prevalence of metabolic syndrome (MetS) in the Polish arm of the Health, Alcohol and Psychosocial factors In Eastern Europe cohort study.MethodsA cross-sectional population-based survey including 8821 adults (51.4 % female) was conducted in Kraków, Poland. Dietary polyphenol intake was evaluated using food frequency questionnaires and matching food consumption data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
78
2
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(93 citation statements)
references
References 60 publications
8
78
2
5
Order By: Relevance
“…Grosso et al published a cohort study in 2016 on another 10,000 Polish subjects, demonstrating an interesting inverse association between polyphenols and metabolic syndrome, which is particularly evident in individuals with the biggest intake of these [22]. …”
Section: Cardiovascular Benefits Of Citrus Flavanones—epidemiologimentioning
confidence: 99%
“…Grosso et al published a cohort study in 2016 on another 10,000 Polish subjects, demonstrating an interesting inverse association between polyphenols and metabolic syndrome, which is particularly evident in individuals with the biggest intake of these [22]. …”
Section: Cardiovascular Benefits Of Citrus Flavanones—epidemiologimentioning
confidence: 99%
“…Daily consumption of (poly)phenols has been related to reduction of inflammation, hypertension, risk of cardiovascular, metabolic, neurodegenerative diseases, and cancer [18,19,20,21,22]. An essential part of the scientific research in vivo is represented by the investigation of the absorption, metabolism and bioavailability of (poly)phenolic compounds after human intake.…”
Section: Introductionmentioning
confidence: 99%
“…72 HCA intake was also associated with lower odds of depression in an Italian cohort, although not in a linear dependence on concentration, 73 and with lower odds of developing metabolic syndrome in a Polish cohort. 74 Other two studies conducted in Iran showed no association between phenolic acid intake and metabolic syndrome; 75,76 however, the reported intake of phenolic acids in the Iranian studies was much lower than that in the Polish study. 74 A reduced risk of diabetes in elderly persons at high risk of CVD was associated with a high intake of total polyphenols in a Spanish cohort.…”
Section: Hydroxycinnamic Acids and Disease Risk In Epidemiological Stmentioning
confidence: 92%
“…flavonoids, have a much longer research history in terms of epidemiological evidence of their health effects. [64][65][66] Regarding phenolic acids, recent cohort studies ( Table 2) have focused mainly on cardiovascular disease (CVD), [67][68][69] hypertension, [70][71][72] depression, 73 metabolic syndrome, [74][75][76] diabetes, 77 and colorectal cancer. 78 A higher intake of polyphenols was associated with a statistically significant decrease in CVD risk in two studies from France and Spain, 67,69 whereas no association was found in the third.…”
Section: Hydroxycinnamic Acids and Disease Risk In Epidemiological Stmentioning
confidence: 99%